No association between 3 polymorphisms of transforming growth factor beta3 gene and essential hypertension in Chinese - Hu, Bang-Chuan; Chu, Shao-Li; Wang, Ji-Guang; Wang, Gu-Liang; Gao, Ping-Jin; Zhu, Ding-Liang (Zhōnghuá xīnxuèguănbìng zázhì, 2005)
To investigate possible association between the single nucleotide polymorphisms (SNPs) of transforming growth factor beta3 (TGF-beta3) gene and essential hypertension (EH) in Chinese. The promoter region, exons, as well as part of the introns of TGF-beta3 gene were sequenced by a fluorescent labeling automatic sequencing method to detect and characterize the SNPs in 24 DNA samples from a Chinese population. Then we conducted a case-control study using 396 patients with hypertension (case) and 214 nomortensive subjects (control). The three SNPs including Thr63Asn, SS5608219 and SS5608220 were genotyped by PCR-RFLP or real-time allele-specific PCR in subjects studied. Seven SNPs in the exons, introns and 3'untranslated region (3'UTR) of TGF-beta3 gene were identified. Among them, 2 SNPs were found to be novel genetic variants and one of the two located in the exon 1 and produced substitution of amino acid. However, no differences were found between hypertensives and nomortensives in genotype distribution and al